Military Connections, Investment Efficiency and Political Uncertainty: Evidence from Pakistan - Muhammad Saif ul Islam; Woei-Chyuan Wong; Mohd Yushairi bin Mat Yusoff (Asian Academy of Management Journal of Accounting and Finance, 2024)
This study examined the impact of military connections on a firm's investment efficiency in Pakistan during the period from 2011 to 2019. Fixed effect regression results revealed that military connections exert a positive and significant effect on the firm's investment efficiency, supporting the resource dependence theory's prediction. This result remains robust when using alternative measurements of investment efficiency, considering periods of political uncertainty proxied by election years, and controlling for endogeneity issues related to the military connection variable. However, a breakdown of military connections revealed that the presence of a military-connected Chairman reduces firms' investment efficiency. Our paper contributes to the growing attention on the impact of military-connected key individuals on corporate decision-making.